Facies and evolution of the carbonate factory during the Permian–Triassic crisis in South Tibet, China. Issue 7 (30th May 2019) - Li, Mingtao; Song, Haijun; Woods, Adam D.; Dai, Xu; Wignall, Paul B.
Abstract: The nature of Phanerozoic carbonate factories is strongly controlled by the composition of carbonate‐producing faunas. During the Permian–Triassic mass extinction interval there was a major change in tropical shallow platform facies: Upper Permian bioclastic limestones are characterized by benthic communities with significant richness, for example, calcareous algae, fusulinids, brachiopods, corals, molluscs and sponges, while lowermost Triassic carbonates shift to dolomicrite‐dominated and bacteria‐dominated microbialites in the immediate aftermath of the Permian–Triassic mass extinction. However, the spatial–temporal pattern of carbonates distribution in high latitude regions in response to the Permian–Triassic mass extinction has received little attention. Facies and evolutionary patterns of a carbonate factory from the northern margin of peri‐Gondwana (palaeolatitude ca 40°S) are presented here based on four Permian–Triassic boundary sections that span proximal, inner to distal, and outer ramp settings from South Tibet. The results show that a cool‐water bryozoan‐dominated and echinoderm‐dominated carbonate ramp developed in the Late Permian in South Tibet. This was replaced abruptly, immediately after the Permian–Triassic mass extinction, by a benthic automicrite factory with minor amounts of calcifying metazoans developed in an inner/middle ramp setting, accompanied by transient subaerial exposure. Subsequently, an extensive homoclinal carbonate ramp developed in South Tibet in the Early Triassic, which mainly consists of homogenous dolomitic lime mudstone/wackestone that lacks evidence of metazoan frame‐builders. The sudden transition from a cool‐water, heterozoan dominated carbonate ramp to a warm‐water, metazoan‐free, homoclinal carbonate ramp following the Permian–Triassic mass extinction was the result of the combination of the loss of metazoan reef/mound builders, rapid sea‐level changes across Permian–Triassic mass extinction and profound global warming during the Early Triassic.